Modeling adsorption of simple fluids and hydrocarbons on nanoporous carbons. (September 2022) - Corrente, Nicholas J.; Hinks, Elizabeth L.; Kasera, Aastha; Gough, Raleigh; Ravikovitch, Peter I.; Neimark, Alexander V.
Abstract: Predicting adsorption on nanoporous carbonaceous materials is important for developing various adsorption and membrane separations, as well as for oil and gas recovery from shale reservoirs. Here, we explore the capabilities of 3D molecular models of disordered carbon structures to reproduce the morphological and adsorption features of practical adsorbents. Using grand canonical Monte Carlo simulations, we construct a series of adsorption isotherms of simple fluids (N2, Ar, CO2, and SO2 ) and a series of alkanes from methane to hexane on two model 3D structures, purely microporous structure A and micro-mesoporous structure B. We show that structure A reproduces the morphological properties of commercial Norit R1 Extra activated carbon and demonstrates outstanding agreement between the simulated and experimental adsorption isotherms reported in the literature for all adsorbates considered. Good agreement is also found for simulated and measured isosteric heats. Taking into account inherent variability of structural properties of commercial carbons and experimental adsorption data from different literature sources, the correlations with experiments are truly amazing. This work provides a new insight into the specifics of structural and adsorption properties of nanoporous carbons and demonstrates the advantages of using 3D molecular models for predicting adsorption hydrocarbons and other chemicals by MC simulations. Graphical abstract: Image 1 Highlights: 3D molecular models replicate morphological specifics of nanoporous carbons characterized by geometric and adsorption methods. Monte Carlo generated isotherms of adsorption of simple fluids and hydrocarbons are in good agreement with experimental data on Norit R1 Extra. Monte Carlo simulations on 3D models reveal the mechanisms of gas adsorption on micro-mesoporous carbons not seen with standard adsorption models.